COVID-19 research priorities for non-pharmaceutical public health and social measures. (5th April 2021) - Semenza, Jan C.; Adlhoch, Cornelia; Baka, Agoritsa; Broberg, Eeva; Cenciarelli, Orlando; De Angelis, Stefania; Einoder-Moreno, Margot; Dalmau, Irina Jovel Quinonez; Kinross, Pete; Kinsman, John; Leitmeyer, Katrin; Melidou, Angeliki; et al.
Abstract: Europe is in the midst of a COVID-19 epidemic and a number of non-pharmaceutical public health and social measures have been implemented, in order to contain the transmission of severe acute respiratory syndrome coronavirus 2. These measures are fundamental elements of the public health approach to controlling transmission but have proven not to be sufficiently effective. Therefore, the European Centre for Disease Prevention and Control has conducted an assessment of research gaps that can help inform policy decisions regarding the COVID-19 response. We have identified research gaps in the area of non-pharmaceutical measures, physical distancing, contact tracing, transmission, communication, mental health, seasonality and environment/climate, surveillance and behavioural aspects of COVID-19. This prioritisation exercise is a step towards the global efforts of developing a coherent research road map in coping with the current epidemic but also developing preparedness measures for the next unexpected epidemic.